Understanding the challenge of weight loss maintenance: a systematic review and synthesis of qualitative research on weight loss maintenance. Issue 2 (3rd April 2017) - Greaves, Colin; Poltawski, Leon; Garside, Ruth; Briscoe, Simon
ABSTRACT: Behaviour change interventions can be effective in helping people to lose weight, but weight is often regained. Effective interventions are required to prevent this. We conducted a systematic review and synthesis of qualitative research on people's experiences of weight loss maintenance. We searched bibliographic databases for qualitative studies about the experience of currently or previously overweight adults trying to maintain weight loss. We thematically synthesised study findings to develop a model of weight loss maintenance. Twenty six studies from five countries with 710 participants were included. The model developed through our synthesis proposes that making the behaviour changes required for weight loss maintenance generates psychological 'tension' due to the need to override existing habits, and incompatibility of the new behaviours with the fulfilment of psychological needs. Successful maintenance involves management or resolution of this tension. Management of tension can be achieved through self-regulation, renewing of motivation and managing external influences, although this can require constant effort. Resolution may be achieved through changing habits, finding non-obesogenic methods for addressing needs, and potentially through change in self-concept. Implications for the development of weight loss maintenance interventions are explored.